1994
DOI: 10.1021/j100074a026
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Hydrogen Chloride with an Ultrathin Ice Film: Observation of Adsorbed and Absorbed States

Abstract: With the objective of gaining insight into how heterogeneous reactions occur in the Antarctic stratosphere, we have initiated a program to study the adsorption and reaction of simple molecules on model polar stratospheric cloud surfaces. In this work, the temperature-programmed desorption of hydrogen chloride from ultrathin (5-20 monolayers thick) water films is described. Two distinct HC1 desorption states, designated a-and 0-HCl, are observed a t 140 and 180 K, respectively. Water sublimation occurs at 180 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
172
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(195 citation statements)
references
References 8 publications
22
172
0
1
Order By: Relevance
“…To date, TP-TOF-SIMS has revealed that both HCl and NH 3 molecules adsorbed on pure ASW films are hydrated considerably up to 140 K [22][23][24], which is consistent with the conclusions drawn using different approaches [3][4][5][6]8,9,13,14]. However, very little is known about intermolecular interactions at the surface of acidic and basic water-ice films including hydrated HCl or NH 3 molecules, respectively.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…To date, TP-TOF-SIMS has revealed that both HCl and NH 3 molecules adsorbed on pure ASW films are hydrated considerably up to 140 K [22][23][24], which is consistent with the conclusions drawn using different approaches [3][4][5][6]8,9,13,14]. However, very little is known about intermolecular interactions at the surface of acidic and basic water-ice films including hydrated HCl or NH 3 molecules, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Molina et al [1] proposed that the reaction rate between HCl and ClNO 2 is enhanced considerably by the existence of ice particles, but detailed reaction pathways for the ionization and solvation of HCl adsorbed on a water-ice surface are not yet fully understood. So far, a number of groups have been extensively tackling these fascinating topics by infrared spectroscopy (IR) [3][4][5][6][7][8][9], reactive Cs + ion scattering (RIS) [10,11], near edge X-ray absorption fine structure (NEXAFS) [12], and temperature-programmed desorption (TPD) [8,9,13,14] analyses, and computer simulations [3,5,[15][16][17][18][19][20][21]. Recently, arguments tend to converge on the conclusion that both the ionization and solvation of HCl molecules occur as proposed by Devlin and coworkers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…41,42 It should be pointed out that at the temperatures studied by Graham and Roberts ice micropores are thermodynamically unstable and rapidly collapse. 25 Graham and Roberts reported that the uptake of HCl on amorphous and crystalline ice films at 120 K results in the formation of a crystalline HCl‚6H 2 O hydrate layer.…”
Section: Discussionmentioning
confidence: 98%
“…Their bulk properties, for instance, their sublimation energies and infrared optical constants, are indistinguishable from those of macroscopic samples of the same temperature and composition. 13,[15][16][17] Also, for films of nominal thickness greater than ∼5 ML, the substrate is completely masked from the gas phase, and beyond ∼10 ML the substrate has no discernible influence on the structure or properties of a film. 15,18 There are several reasons for studying the surfaces of ultrathin films rather than those of macroscopic samples.…”
Section: Experimental Approachmentioning
confidence: 99%